Fresh Produce Handling, Sanitation, and Safety Measures: Beans, Cucumbers, Eggplants, Squash, Peppers, Sweetcorn - M. Mahovic; Jeffrey Brecht; Steven Sargent; Mark Ritenour; Keith Schneider; Amy Simonne; Jerry Bartz (EDIS)
This document is FSHN0213, one of a series of the Food Science and Human Nutrition Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication: October 2002.